Mazie - Crowder, Melanie (Viking, 2022)
Seventeen-year-old Mazie Butterfield leaves her family and boyfriend behind in small-town Nebraska to find fame on 1950s Broadway, but when her big break comes it means going back to the Corn Belt and facing her past.